The Semantic Analysis of Slang in The Movie “School” (Journal of Pedagogical Inventions and Practices, 2021)
The given article is about the notions of scholars about slang and the reasons of using them, it’s classification, it’s popularity among the youth and it’s semantic analyzes according to the movie “School” produced by Uzbek filmmakers.